The category of freedom in the main philosophical conceptions of XXth c. — beginning XXIth c. - Korupyatnik, Iryna (Actual Problems of Mind, 2017)
The paper presents an analysis of some pecularities in the modern philosophical conceptions of freedom. In particular, this category is considered in the contexts of classical and non-classical philosophical traditions, and some differences in its treating by rational and irrational traditions of XXth c. — beginning XXIth c. are elucidated.